Effects of trenching on growth and survival of planted Shorea parvifolia seedlings under pioneer stands in a logged-over forest - Pinard, M. A. (Sabah Forestry Department, 1998)
We conducted an experiment to determine the value of trenching in reducing potentially negative effects of root competition on growth of Shorea parvifolia seedlings planted in the understory of a 13-y-old logged-over forest. Two hundred 1-y-old nursery-raised seedlings were planted in four sites; two sites were in forests logged by high-lead cable yarding, and two were in forests logged using bulldozers for yarding. The ground was trenched (diameter = 1 m) around half of the seedlings in each site to reduce root competition. At 6 months after planting, no effect of trenching treatment was evident on seedling survival or relative height growth for either type of yarding method. Relative growth rates were positively correlated with canopy openness. Although the canopy in the bulldozer yarding sites was more open (15% open) than that in the cable yarding sites (12% open), relative growth rates were greater in cable yarding than in bulldozer yarding sites. At 12 months after planting, relative height growth was similar for trenched and control seedlings and for the two yarding methods. Survival was independent of trenching treatment and was higher in cable yarding than in bulldozer yarding sites. Soil disturbance associated with bulldozer yarding may negatively affect seedling establishment even 13 y after harvest, indicating the importance of pre-harvest planning in reducing the area traversed by bulldozers. Our results suggest that below-ground competition does not limit growth and survival of dipterocarp seedlings in pioneer tree stands. For both trenched and control seedlings, relative growth rates were lower during drier than wetter periods. We recommend that foresters working in drought-prone regions, such as eastern Sabah, explore methods of increasing seedling drought tolerance before outplanting, perhaps by increasing root:shoot ratios, rather than by attempting to reduce below-ground competition by trenching around seedlings in the field.